Analog Circuit Theory and Filter Design in the Digital World With an Introduction to the Morphological Method for Creative Solutions and Design - Moschytz, George S. (Springer International Publishing : Imprint: Springer, 2019)
This textbook is designed for graduate-level courses, and for self-study, in analog and sampled-data, including switched-capacitor, circuit theory and design for ongoing, or active electrical engineers, needing to become proficient in analog circuit design on a system, rather than on a device, level. After decades of experience in industry and teaching this material in academic settings, the author has extracted many of the most important and useful features of analog circuit theory and design and presented them in a manner that is easy to digest and utilize. The methodology and analysis techniques presented can be applied to areas well beyond those specifically addressed in this book. This book is meant to enable readers to gain a 'general knowledge' of one aspect of analog engineering (e.g., that of network theory, filter design, system theory and sampled-data signal processing). The presentation is self-contained and should be accessible to anyone with a first degree in electrical engineering. Presents material in the form of slides, with accompanying text; Demonstrates how the design of many circuit devices, e.g. gyrators, impedance converters, etc. can be accomplished easily, using the 'Morphological Method'; Includes numerous examples from different fields, e.g. circuit devices, active-RC and switched-capacitor circuits and filters, etc.; Emphasizes creative design methods and techniques.